DEVELOPMENT OF MATHEMATICS LEARNING DEVICES BASED ON PROBLEM-BASED LEARNING ON THE MATERIAL OF POLYHEDRON FOR CLASS VIII SMP/MTs STUDENTS - Evi Afrina Widayati Siahaan; Armis (Jurnal Prinsip Pendidikan Matematika, 2022)
This research aims to produce mathematics learning tools in the form of syllabus, lesson plans (RPP), and student worksheets (LKPD) based on learning models based on the problem of building flat side spaces for 8th-grade students of junior high school. This research uses a 4-D development model which includes four stages, namely: (1) define (defining); (2) design (planning); (3) develop (development); and (4) disseminate (spread). The research instrument used is the instrument of validity and practicality. The validity instrument is in the form of a validation sheet to assess the feasibility of the syllabus, lesson plans, and LKPD. The practical instrument is in the form of a student response questionnaire to the use of LKPD. The learning tools that have been compiled are then validated by three validators and revised according to suggestions from the validators. The valid learning tools were then tested in small groups with the subject of 6 students in grade 8th junior high school. Based on the data analysis and discussion results, mathematics learning tools in the form of Syllabus, RPP and LKPD based on learning models based on problems in the flat-sided space building material are considered very valid and practical to be used by 8th-grade students of junior high school.